Potensi Limbah Tahu untuk Menghasilkan Listrik pada Tiga Model Sistem Microbial Fuel Cell (MFC): Tofu Wastewater Potency for Generating Electricity Using Three Models of Microbial Fuel Cell (MFC) - Amanda Kusuma Dewi; Gunawan Djajakirana; Dwi Andreas Santosa (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2020)
Organic waste from tofu industries in general is only thrown into the surrounding river flow and not utilized by the community. Tofu liquid waste contains a lot of protein, so in the decomposition process it produces ammonia which is causes odor. A lack of researchers who understand that tofu waste can also be used as a substrate in Microbial Fuel Cells (MFC). MFC is a system or device that uses bacteria as a catalyst to oxidize organic and inorganic materials. Electrons are produced by bacteria from the substrate which is transferred to the anode (negative pole) and flowed to the cathode (positive pole), then connected by conductivity devices including resistors or operated under charge to produce electricity. The purpose of this study were knowing the effect of using tofu waste as a substrate in the anode on electric currents in MFC also knowing the most effective MFC modeling and providing electricity with the highest current. The result showed that MFC modeling which is considered the most effective and produces the highest voltage is the dual chamber system with Nafion. MFC dual chamber with Nafion isolate Staphylococcus saprophyticus was able to produce a voltage value of 3.74x105 mV and a power density value of 2.87x104 mW m-2.